Den argumentative teksttype i reklamer - Nielsen, Anne Ellerup (HERMES - Journal of Language and Communication in Business, 1998)
The text-typology model developed by Jean-Michel Adam is one of the most well-defined and operational models if one wants to categorize whole texts or text fragments into smaller units. Given that a texttype is the result of specific functional and structural relations between micro- and macropropositions, it is a multicriterial model which takes into account both the syntactic, semantic and pragmatic features of texts. How-ever, the model seems to offer some problems in establishing the limits between the argumentative and the descriptive text type. This imprecision is apparently due to the lack of distinction between the discourse potential of evaluative and referential pro-positions. This problem will be demonstrated on examples from the genre of ad-vertising material which, because of its persuasive purpose, is particularly rich in argumentative features.